Mechanical properties of a cemented porous implant interface. (September 2014) - Beckmann, Nicholas A; Bitsch, Rudi G; Seeger, Joern B; Klotz, Matthias CM; Kretzer, Jan Philippe; Jaeger, Sebastian
<x xml:space="preserve">Abstract</x> Background — Revision arthroplasty often requires anchoring of prostheses to poor-quality or deficient bone stock. Recently, newer porous materials have been introduced onto the market as additional, and perhaps better, treatment options for revision arthroplasty. To date, there is no information on how these porous metals interface with bone cement. This is of clinical importance, since these components may require cementing to other prosthesis components and occasionally to bone. Methods — We created porous metal and bone cylinders of the same size and geometry and cemented them in a well-established standardized setting. These were then placed under tensile loading and torsional loading until failure was achieved. This permitted comparison of the porous metal/cement interface (group A) with the well-studied bone/cement interface (group B). Results — The group A interface was statistically significantly stronger than the group B interface, despite having significantly reduced depth of cement penetration: it showed a larger maximum tensile force (effect size 2.7), superior maximum tensile strength (effect size 2.6), greater maximum torsional force (effect size 2.2), and higher rotational stiffness (effect size 1.5). Interpretation — The newer porous implants showed good interface properties when cemented using medium-viscosity bone cement. The axial and rotational mechanical strength of a porous metal/cement interface appeared to be greater than the strength of the standard bone/cement interface. These results indicate that cementing of porous implants can provide great stability in situations where it is needed.